Comparison of Two Drainage Systems on Chronic Subdural Hematoma Recurrence - Takroni, Radwan; Zagzoog, Nirmeen; Patel, Nimita; Martyniuk, Amanda; Singh, Sheila; Farrokhyar, Forough; Trivedi, Arunachala; Alotaibi, Mazen; Algird, Almunder (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background Chronic subdural hematoma (CSDH) is a common type of intracranial hemorrhage, especially among the elderly, with a recurrence rate as high as 33%. Little is known about the best type of drainage system and its relationship with recurrence. In this study, we compare the use of two drainage systems on the recurrence rate of CSDH.Methods We retrospectively analyzed the charts of 172 CSDH patients treated with bedside twist drill craniostomy (TDC) and subdural drain insertion. Patients were divided into two groups: group A (n = 123) received a pediatric size nasogastric tube [NGT]), whereas group B (n = 49) had a drain commonly used for external ventricular drainage (EVD). Various demographic and radiologic data were collected. Our main outcome was recurrence, defined as symptomatic re-accumulation of hematoma on the previously operated side within 3 months.Results In all, 212 cases of CSDH were treated in 172 patients. The majority of patients were male (78%) and had a history of previous head trauma (73%). Seventeen cases had recurrence, 11 in group A and 6 in group B. The use of antiplatelet and anticoagulation agents was associated with recurrence (p = 0.038 and 0.05, respectively). There was no difference between both groups in terms of recurrence (odds ratio [OR] = 1.42; 95% confidence interval [CI]: 0.49–4.08; p = 0.573).Conclusion CSDH is a common disease with a high rate of recurrence. Although using a drain postoperatively has shown to reduce the incidence of recurrence, little is known about the best type of drain to use. Our analysis showed no difference in the recurrence rate between using the pediatric size NGT and the EVD catheter post-TDC.
Keywords: chronic subdural hematoma; twist drill craniostomy; drainage; recurrence